Uriarte, Javier. The Desertmakers. Travel, War, and the State in Latin America. Routledge, 2020, 324 pp. - Mariana Moraes (Perífrasis. Revista de Literatura, Teoría y Crítica)
Reseña de Uriarte, Javier. The Desertmakers. Travel, War, and the State in Latin America. Routledge, 2020, 324 pp.